PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK COGNITIF BEHAVIOR THERAPY (CBT) TERHADAP KONFLIK INTERPERSONAL MAHASISWA PRODI BK DI UMN AL-WASHLIYAH MEDAN - Nursyadila Purba; Nur Asyah; Vinda Chairunnisa; Ika Sandra Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interpersonal conflict is an ongoing conflict arising from incompatible differences in perspective between individuals. This study aims to determine the effect of group counseling services utilizing Cognitive Behavioral Therapy (CBT) techniques on the interpersonal conflict experienced by students in the Guidance and Counseling Study Program at UMN Al-Washliyah Medan. Group counseling based on the CBT approach plays a crucial role by emphasizing the interrelationship between thoughts, feelings, and behaviors, and by helping individuals identify and alter negative or irrational thought patterns that drive maladaptive behaviors. The study employs a quantitative approach using a pre-experimental "one-group pretest-posttest" design, with data analysis facilitated by SPSS version 20 for Windows. The study population consisted of 19 students, from which a sample of 10 students exhibiting high levels of social interaction was selected using purposive sampling. Hypothesis testing and data analysis revealed a mean pretest score of 91.70 and a mean posttest score of 63.30, indicating a reduction in interpersonal conflict of 28.400. Thus, it can be concluded that this intervention is effective in helping students reduce the interpersonal conflict they experience. These findings are expected to serve as a reference for guidance and counseling educators in designing appropriate counseling services to mitigate student interpersonal conflict on campus.